PERSPECTIVE ON THE STUDY OF THE PROTECTION AND EDUCATION OF MUMAYYIZ CHILDREN IN MARRIAGE ISSUE - Nurhimmi Falahiyati; Jelly Leviza (Sean Institute, 2023)
The marriage law actually regulates all goodness for married couples who are legally bound according to their respective religions and beliefs according to this law with the hope of prosperity and happiness in the marriage. Marriages that break up due to divorce often result in children who don't know anything, who end up becoming victims and not getting the protection they deserve. With so many cases of divorce at a young age of marriage, there are many children who are victims of divorce who still really need protection from their parents. The aim of this research is to find out the legal arrangements regarding child protection in Indonesia, the position of children who have not yet mumayyiz due to the breakdown of marriage and legal protection for children who have not mumayyiz due to the breakdown of marriage (analysis of Decision Number 0678/Pdt.G/2014/PA.Bkn). Based on the research results, it can be concluded that legal regulations regarding child protection in Indonesia are regulated in various applicable laws and regulations, including the 1945 Constitution, Law Number 1 of 1974 concerning Marriage, Law Number 23 of 2003 concerning Protection. Children in conjunction with Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2003 concerning Child Protection. The position of children who are not yet mumayyiz due to the breakdown of the marriage.